The translation studies reader (Routledge, 2000)
he Translation Studies Reader provides a definitive survey of the most important and influential developments in translation theory and research, with an emphasis on twentieth-century developments. With introductory essays prefacing each section, the book places a wide range of seminal and innovative readings within their thematic, cultural and historical contexts.